Segurança do paciente no processo de vacinação pelo sistema drive-thru no contexto da pandemia da covid-19 no sul do Brasil - Oliveira, Ana Paula Ribeiro de (2024)
Introduction: The health crisis caused by COVID-19 has led authorities to plan various coping actions, including vaccination via the drive-thru system. This system highlighted the need to better understand this activity. Objective:To analyze the building vaccination process using the drive-thru system during the COVID-19 pandemic in southern Brazil with focus in patient safety. Method: Thisqualitative research was developed through a field study (descriptive and exploratory method), using virtual and individual interviews according to a semi-structured script. A non-probability sampling (“snowball” technique) was used to obtain saturation of findings. They were organized and analyzed using the NVIVO® software (v. 12). The study population consisted of workers who directly or indirectly worked and/or work in vaccination using the drive-thrusystem during the COVID-19 pandemic in the Municipalities of Porto Alegre (RS) and Florianópolis (SC). Results: In the southern region of Brazil, thevaccination during the COVID-19 pandemic began as punctual experiments that were carried out in a tumultuous manner due to the lack of experience in the drive-thrusystem. However, it was structured and improved during the process to better serve local populations. The Nursing work in the organization, management, maintenance, and administration was a highlight in achieving records of vaccination coverage using this innovative system despite the existing challenges (insufficient inputs, misinformation, professional burnout, etc.) during the implementation of drives. Conclusion: The Nursing team showed to be essential in the vaccination operationalizationusing the drive-thrusystem during the COVID-19 pandemic. New studies are still needed to propose a drive-thruvaccination protocol and obtain a valid instrument to assess the perception of patient safety among vaccinators in the drive-thrusystem aiming to implement this system in future mass vaccination campaigns on the Brazilian scene as a strategy in the National Immunization Program